Double osseous flaps for simultaneous midfacial and mandible reconstruction: Automation in surgical complexity within an entirely computerized workflow - Tel, Alessandro; Bagatto, Daniele; Sembronio, Salvatore; Ferrari, Silvano; Robiony, Massimo (Frontiers in Oncology, 2023)
Introduction Broad maxillofacial surgical resections involving both the midface and the mandible represent a challenge in terms of reconstruction. Although several papers have explored the possibility of simultaneously using two microsurgical flaps, reports on the implementation of a dual osseous flap strategy are limited, and mainly addressed to static anatomical reconstruction, regardless of functional implications. In particular, there is a lack in the literature of a unifying protocol which illustrates how technology including virtual planning, statistical shape modeling, virtual occlusion, 3D-printing and patient-specific implants can address the functional and accuracy needs required for an optimal reconstruction. Materials and methods In this paper, the Authors present their preliminary experience in a two-center study, showing how broad maxillofacial defects, requiring a simultaneous reconstruction in both the mandible and the midface, can be successfully reconstructed using the combination of two osseous flaps in an automated sequence in which all steps are anticipately defined in a virtual plan, accounting for the optimal alignment of temporomandibular joint, predicting the final occlusion and defining a mandibular shape according to a statistical shape model. Results Average RMSE for the iliac bone crest flap was of 3.2 ± 0.36 mm; for the fibula flap, RMSE value was of 2.3 ± 0.65 mm, for patient-specific implants, for mandibular prostheses the average RMSE was 2.46 mm with 0.76 mm standard deviation. Temporomandibular joint function increased when a TMJ prosthesis was placed. Conclusions Double bone free flap is a valuable resource to reconstruct wide defects that simultaneously involve two thirds of the cranio-maxillo-facial skeleton, but a careful virtual planning study should be always performed before approaching this surgical option.